Predictors of Islamic Financial Inclusion in the Northwest Nigeria: A Preliminary Cross-Sectional Investigation - Aliyu, Shehu Usman Rano; Danlami, Abubakar Hamid; Shehu, Farida Mohammed (Universitas Muhammadiyah Yogyakarta, 2024)
Financial inclusion is seen widely as a tool for attaining macroeconomic objectives of economic growth, poverty reduction, economic prosperity, and the like. The phenomenon of Islamic financial inclusion is a decade old in Nigeria. As prelude (pilot) to broader study, this paper conducts a preliminary assessment of predictors of Islamic financial inclusion in the Northwest zone which is composed of seven (7) states in Nigeria. Leveraging on expositions in both the theoretical and empirical literature on dimensions of financial inclusion; access, use, quality, and barriers, this study constructs three logistic regression models based on access to financing facilities, access through automated teller machine (ATM), and access using unstructured supplementary service data (USSD) banking code. Results show that while the access to financing logistic model outperforms the other two models, household’s location and years of business (YOB) experience were statistically significant across all three models implying that those in the urban areas and with more years of business experience tend to be more financially included than their counterparts in the rural areas. In line with intuition, age of the household and YOB experience are averse to the use of ATM card and USSD code for banking transactions. The paper recommends improved infrastructure provision and increased reach to rural areas through innovative banking service delivery to enhance financial inclusion in the zone. This study is among earliest attempts that assesses the predictors of Islamic financial inclusion in the Northwest, Nigeria.